Sleep Disturbance in Older Patients in the Emergency Department: Prevalence, Predictors and Associated Outcomes - Mannion, Helen (Int J Environ Res Public Health, 2019)
Impaired sleep is common in hospital. Despite this, little is known about sleep disturbance among older adults attending Emergency Departments (ED), particularly overnight-boarders, those admitted but housed overnight while awaiting a bed. Consecutive, medically-stable patients aged ≥70, admitted through a university hospital ED were evaluated for overnight sleep quality (Richards Campbell Sleep Questionnaire/RCSQ) and baseline sleep (Pittsburgh Sleep Quality Index/PSQI). Additional variables included frailty, functional and cognitive status, trolley location, time in ED and night-time noise levels. Over four-weeks, 152 patients, mean age 80 (± 6.8) years were included; 61% were male. Most (68%) were ED boarders (n = 104) and 43% were frail. The majority (72%) reported impaired sleep quality at baseline (PSQI ≥ 5) and 13% (20/152) had clinical insomnia. The median time spent in ED for boarders was 23 h (Interquartile ± 13). After adjusting for confounders, median RCSQ scores were significantly poorer for ED boarders compared with non-boarders: 22 (± 45) versus 71 (± 34), respectively, (p = 0.003). There was no significant difference in one-year mortality (p = 0.08) length of stay (LOS) (p = 0.84), 30-day (p = 0.73) or 90-day (p = 0.64) readmission rates between boarders and non-boarders. Sleep disturbance is highly prevalent among older adults admitted through ED. ED boarders experienced significantly poorer sleep, without this impacting upon mortality, LOS or re-admission rates.